2019
DOI: 10.1111/jfb.14222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β‐1/3,1/6‐glucan upon immune responses and bacteria in the gut of healthy common carp (Cyprinus carpio)

Abstract: β-glucans are frequently included in the diet of healthy common carp Cyprinus carpio as a pre-emptive measure for combatting disease. In order to study the effect this has on the relationship between the gut bacteria and host immune response, carp were maintained on either a β-glucan free diet or feed containing 0.1% MacroGard ® , a β-1/3, 1/6-glucan, for up to 7 weeks and analysis of innate immune gene expression and molecular analysis of the gut bacteria was performed. The data reveals feeding of MacroGard ®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Interestingly, analysis of microbiota composition following oral gavage with b-glucans in vivo revealed no alteration of the composition, arguing that a single oral gavage with b-glucans will not alter the composition, but can alter the metabolism. In contrast to other studies investigating the effects of b-glucans on fish microbiota composition, those studies investigated the effect of constant exposure during dietary supplementation (27)(28)(29)(30)(31)(32)(33). Our microbiota sequencing data confirm the presence of bacterial genera commonly associated with b-glucan-fermenting capacity.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, analysis of microbiota composition following oral gavage with b-glucans in vivo revealed no alteration of the composition, arguing that a single oral gavage with b-glucans will not alter the composition, but can alter the metabolism. In contrast to other studies investigating the effects of b-glucans on fish microbiota composition, those studies investigated the effect of constant exposure during dietary supplementation (27)(28)(29)(30)(31)(32)(33). Our microbiota sequencing data confirm the presence of bacterial genera commonly associated with b-glucan-fermenting capacity.…”
Section: Discussionsupporting
confidence: 61%
“…In seabass, a 4-week feeding with β-glucan-enriched diets induced a shift toward more Methylobacterium ( 29 ), whereas in rainbow trout and feral common carp, an 8-week feeding with yeast-derived probiotics rich in β-glucans induced a shift toward more lactic acid bacteria ( 30 , 31 ). Recently, a study investigating the effect of feeding β-glucans for 7 weeks to common carp showed, through DGGE analysis, a possible shift in bacterial species richness alongside a downregulation of il-1b expression ( 32 ). Also, addition of β-glucans to the water could affect the composition of intestinal microbiota, at least of Nile tilapia ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…155 In zebrafish, studies found that feeding fish diets containing high saponin or soy protein contents can induce significantly increased numbers of granulocytes. 156 Additionally, Harris et al 157 found supplementation of Cyprinus carpio with β-glucan could change bacterial composition in the gut. These results might show potential correlation between granulocytes and fish microbiota.…”
Section: Innate Cellular Immune Response To Microbiotamentioning
confidence: 99%
“…The black soldier fly ( Ptecticus tenebrifer ) and yellow mealworm ( Tenebrio molitor ) have particularly interesting characteristics as they can valorize organic waste, producing proteins, fats and energy that is exploitable for feed (De Marco et al., 2015). Moreover, the presence of β‐glucanase from the midgut of T. molitor (Genta et al., 2009; Zhang et al., 2003) that are immunomodulants improves health through increased resistance against infection (Harris et al., 2020).…”
Section: Introductionmentioning
confidence: 99%